Villosa / Yazid Othman - Othman, Yazid (Universiti Teknologi MARA, Kedah, 2018)
Vilosa is an armchair. This chair influence by pitcher plant. Pithcer plants whose prey-trapping mechanism feautres a deep cavity filled with liquid known as a pitfall trap. Foraging, flying or crawling in sects such as flies are attracted to the cavity formed by the cupped leaf, often by visual lures such as anthocyanin pigments, and nectar bribes.